Two-step nonlinear optical switch in a hydrogen-bonded perovskite-type crystal. Issue 11 (13th January 2022) - Hua, Xiu-Ni; Zhang, Wan-Ying; Shi, Ping-Ping
Abstract : A perovskite-type crystal with exceptional hydrogen bond interactions exhibits two-step switchable nonlinear optical behaviors, which are associated with the onset of reorientational motion and ordered–disordered transformation of organic cations. Abstract : Switchable nonlinear optical (NLO) materials have aroused broad interest on account of their captivating optical and electronic properties. We demonstrate a novel perovskite-type crystal with exceptional hydrogen bond interactions that are associated with the onset of reorientational motions of organic cations and thus induce the occurrence of two successive phase transitions to be a two-step NLO switch. This finding affords an alternative approach for the design and assembly of switchable NLO materials.